The effect of hydrogen bonds between flow improvers with asphaltene for heavy crude oil. (1st February 2019) - Quan, Hongping; Xing, Langman
Abstract: A series of chemical products with characteristic groups in molecular structures were synthesized as novel flow improvers (FIs) for heavy asphaltenic crude oil. The rheological measurement results showed that the FI-5 could behave the better performance in improving fluidity of heavy oil than FI-2 due to the former could form stronger hydrogen bonds with asphaltene in oil, which was confirmed through Fourier transform infrared spectroscopy (FTIR) and energy of simulating studies. Furthermore, X-ray diffraction (XRD) analysis results demonstrated that two products altered asphaltene structure at different degree through hydrogen bonding interaction, and the aggregation-dispersion effect of FIs on asphaltene were respectively obtained through scanning electron microscope (SEM), which beneficially weakened the stable structure of asphaltene in the heavy crude oil system. Hence, the mechanisms were tried to propose that could explain the phenomenon in rheological measurement why FI-2 was not as good as FI-5 in improving fluidity of heavy oil. Results also indicated that the asphaltene content and aggregation structure in oils were vital parameters for its viscosity.